З історії формування маєткових комплексів князів Чорторийських у Великому князівстві Литовському (кінець XV–XVI ст.) - Блануца, А.; Вікторова, Л. (Український історичний журнал, 2019)
Простежується історія формування маєткових комплексів та управлінської
діяльності представників князівського роду Чорторийських на Волині й у Великому князівстві Литовському наприкінці XV – у XVI ст. Дослідження спирається на комплекс документів родини Чорторийських із зібрання «Західноруські
акти» Російської національної бібліотеки у Санкт-Петербурзі та
матеріали Литовської метрики. Основними дійовими особами, представниками роду Чорторийських, виступають луцький староста князь Федір Михайлович та його син князь Іван Федорович, котрий кілька років (1564–1565 рр.)
тримав уряд справці Київського воєводства. Установлено тісне переплетіння
майнового й суспільного статусу роду в управлінській системі Волині та загалом держави. Рід князів Чорторийських на середину XV ст. посідав одне із пріоритетних місць у соціально-політичній ієрархії реґіону й Великого князівства
Литовського, а зі здобуттям високих урядів почалося стрімке нарощування земельних комплексів і розбудова господарства. The article deals with the complex of documents dedicated to the princely family of
Chortoryiski from the “West Rus Acts” collection of the National Library of Russia in
St. Petersburg which materials cover the period from 1528 to 1646 and documents
of Lithuanian Metrica. The family founder Vasyl Kostiantynovych Chortoryiskyi’s
sons Ivan and Mykhailo were members of the Council of the grand Lithuanian duke
Švitrigaila in the 15th century. Nevertheless, the destiny has parted them in two different
ways. The first one’s heirs received state positions and estates in the Moscow state, the
second one’s – in the Grand Duchy of Lithuania. The “West Rus Acts” represent the
Chortoryiski family of the Lithuanian branch. The main figures involved in property
transactions of the Chortoryiski family were the Lutsk head (1522–1542) prince Fedir
Mykhailovych and his son prince Ivan Fedorovych. Prince Fedir was prince Mykhailo
Vasyliovych’s son who was a marshal of the duke Švitrigaila’s court from 1445 to 1452
and the Bratslav deputy from 1452 and also the grandson of the family’s founder –
prince Vasyl Kostiantynovych Chortoryiskyi. His son prince Ivan Fedorovych (1564–
1565) held the position of spravtsa of the Kyiv palatine for about two years. Together
with prince Ivan his wife, princess Hanna Kuzmivna Zaslavska and his daughter,
princess Olena Ivanivna also are mentioned in documents. Princess Olena became the
wife of the Navahrudak deputy Ostafii Ivanovych Hornostai. The documents, first of
all, are of great value for studying the property aspect of some family representatives,
in particular, Lutsk head Fedir Mykhailovych Chortoryiskyi and his heirs. Property
affairs of Fedir Mykhailovych and his son Ivan Fedorovych reflect the formation, expansion, transfer to inheritance and upholding in courts the princes Chortoryiski patrimonial property fund in the second half of the 16th century.